Association between nutritional guidance or ophthalmological examination and discontinuation of physician visits in patients with newly diagnosed diabetes: A retrospective cohort study using a nationwide database. Issue 9 (28th February 2021) - Okada, Akira; Ono, Sachiko; Yamaguchi, Satoko; Yamana, Hayato; Ikeda Kurakawa, Kayo; Michihata, Nobuaki; Matsui, Hiroki; Nangaku, Masaomi; Yamauchi, Toshimasa; Yasunaga, Hideo; Kadowaki, Takashi
Abstract: Aims/Introduction: Discontinuation of diabetes care has been studied mostly in patients with prevalent diabetes and not in patients with newly diagnosed diabetes, whose dropout risk is highest. Because enrolling patients in a prospective study will influence adherence, we retrospectively examined whether guideline‐recommended practices, defined as nutritional guidance or ophthalmological examination, can prevent patient discontinuation of diabetes care after its initiation. Materials and Methods: We retrospectively identified adults with newly screened diabetes during checkups using a large Japanese administrative claims database (JMDC, Tokyo, Japan) that contains laboratory data and lifestyle questionnaires. We defined discontinuation of physician visits as a follow‐up interval exceeding 6 months. We divided the patients into those who received guideline‐recommended practices (nutritional guidance or ophthalmology consultation) within the same month as the first visit and those who did not. We calculated propensity scores and carried out inverse probability of treatment weighting analyses to compare discontinuation between the two groups. Results: We identified 6, 508 patients with at least one physician consultation for diabetes care within 3 months after their checkup, including 4, 574 patients without and 1, 934 with guideline‐recommended practices. After inverse probability of treatment weighting, patients with guideline‐recommended practices had a significantly lower proportion of discontinuation than those without (17.2% vs 21.8%; relative risk 0.79, 95% confidence interval 0.69–0.91). Conclusions: This study is the first to show that after adjustment for both patient and healthcare provider factors, guideline‐recommended practices within the first month of physician consultation for diabetes care can decrease subsequent discontinuation of physician visits in patients with newly diagnosed diabetes. Abstract : Nutritional or ophthalmological care is recommended in diabetes guidelines. Newly‐screened diabetes patients receiving such care are less likely to discontinue care. Nutritional guidance is especially important among guideline‐recommended practices.